Relationship between Service Quality and Customer Satisfaction in Restaurants in Los Olivos, Peru - Gamarra-Miranda, Miguel Antonio (2022)
The objective of this research is to determine the degree of relationship between the quality of service and customer satisfaction in the restaurants of the Los Olivos district, in the year 2021. The study is based on a quantitative and correlational approach, with a non-experimental design and cross-sectional classification. To measure the two variables, a sample of 381 customers visiting restaurants in Los Olivos was taken. For service quality, the Servqual model was used, and for satisfaction, a tool based on factor analysis was used. A survey of 43 questions with a Likert scale from 1 to 7 was applied, and the following results were obtained: the general hypothesis was accepted with a significant coefficient (p-values < 0.05). Regarding the specific hypotheses, reliability, empathy and tangibles are accepted with significant coefficients (p-values < 0.05) in contrast to the dimensions of responsiveness and safety which are rejected with non-significant coefficients (p>0.05). In conclusion, restaurants should train staff to serve efficiently and improve safety, as well as modernise their facilities and technological capacity to ensure their success.